Avaliação do programa de triagem neonatal para a fenilcetonúria no estado de Sergipe - Ramalho, Antonio Roberto de Oliveira (2011)
The aim of this study was to evaluate the National Neonatal Screening Program in Sergipe State in Brazil Northeastern (PNTN/SE) for phenylketonuria (PKU). It was performed a cross-sectional study. Variables assessed were: phenylalanine blood concentrations at filter paper collected from the heel of 43.449 children (PKUneo); blood phenylalanine concentrations obtained by venipuncture in the children with abnormal PKUneo; children s age in the different program phases from January 2007 to June 2008; and the coverage in 2007. The suspected children were selected when PKUneo were above the cut-off level of 5 mg/dL. Furthermore, these children were classified by the venous concentration of phenylalanine in according to the literature, thereby obtaining the prevalence of hyperphenylalaninemy (HPA) and phenylketonuria from January 2007 to June 2008. The cases diagnosed before 2007 were not analysed. Finally, we verified the venous concentrations of phenylalanine at those children on dietetic treatment for the disease as much as the amount of phenylalanine present on their diet. The children s age at PKUneo collection was 107 days (MDP), the age when the assay was done was 2813 days and at the venous collection in the diagnosis confirmation was 5317 days. Twelve children were called based on the PKUneo cut-off. From these, the concentrations of phenylalanine collected by venipuncture were normal in five children, one child was classified as hyperphenylalaninemy and five as PKU with the prevalence of 1/43449 and 1/8690, respectively. The treatment for PKU began with 5112 days. The coverage of PNTN/SE/2007 was 78.93%, besides, 11% of the Sergipe´s children that have private health care. In conclusion, PNTN/SE presented satisfactory coverage, PKU and hyperphenylalaninemy prevalences compatible with the literature and adequate cut-off. On the other hand, the collection of PKUneo is late and the onset of treatment is delayed.